The indigenous art of orchid noken making by the Mee Tribe in the highland of Central Mountains, Indonesian Papua - YUBELINCE Y. RUNTUBOI; DINA ARUNG PADANG; MARIANA H. PEDAY; AGUSTINA Y. S. AROBAYA; ANTONI UNGIRWALU; AMILDA AURI; PETRUS A. DIMARA; CICILIA M.E. SUSANTI; NOVITA PANAMBE; NITHANEL M.H. BENU (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Runtuboi YY, Padang DA, Peday MH, Arobaya AYS, Ungirwalu A, Auri A, Dimara PA, Susanti CME, Panambe N, Benu NMH. 2023. The indigenous art of orchid noken making by the Mee Tribe in the highland of Central Mountains, Indonesian Papua. Biodiversitas 24: 3881-3890. The eastern Indonesian Papua boasts remarkable biodiversity and valuable natural resources. Despite this, there has been a lack of scientific investigation into the sustainable utilization of these resources by the diverse ethnic groups residing in Papua. This paper discusses the traditional practice of the men of the Mee Tribe, who specialize in crafting a traditional bag called orchid noken. The study aims to document and preserve the local knowledge and expertise of the Mee Tribe regarding the use of plants in their craftwork. The field study was conducted in August 2014 in the village of Bomomani, located in the Dogiyai District of Papua Province. Qualitative methods, such as interviews and participatory observation, were employed to collect data from 18 key informants selected for their knowledge of the Mee Tribe's traditional practices of orchid noken making. The study uncovered that the Mee Tribe relies on nine species of wild plants, including orchids, ferns, and rattans, as the primary raw materials for crafting noken. Specific parts of these plants are carefully selected and incorporated into the crafting process, employing different processing techniques to achieve the desired colors and textures in the final product. The findings highlight the immense significance of the orchid noken in the daily lives of the Mee Tribe. This study demonstrates that noken is a product closely associated with the local knowledge and culture of the Mee Tribe. Additionally, by documenting and understanding the Mee Tribe's traditional practices, the research contributes to the conservation of plant diversity and the preservation of Papuan cultural heritage. This study ensures the continued transmission of traditional knowledge and practices to future generations, safeguarding the invaluable cultural heritage of Papuans.